The Influence of First Language on Students’ English Speaking Difficulties at SMAN 12 Medan - Bahagia Saragih; Barli Kifli; May Rani Gresya Barus; Theo Josep Grasio Sipahutar; Rika Lestari br Sembiring; Uswatun Habibah; Fania Zahra Batubara; Partahi Josua Parhusip (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study explores the role of the first language in English learning among students at SMAN 12 Medan. The research aims to analyze how the mother language influences students’ speaking performance in learning English as a foreign language. A descriptive qualitative method was applied in this study involving 35 eleventh-grade students of SMAN 12 Medan. The data were obtained through questionnaires and students’ responses related to speaking activities. The findings indicate that students still experience several difficulties in speaking English, including vocabulary limitations, grammar problems, pronunciation difficulties, speaking anxiety, and low selfconfidence. Vocabulary was identified as the most dominant problem faced by students during communication activities. The results also show that many learners tend to use their first language as support when they have difficulties expressing ideas in English. Example , students applied several communication strategies such as using fillers, asking for help, using gestures, and simplifying sentences in order to maintain communication. These strategies helped students continue speaking despite their language limitations. The study concludes that the first language remains an important factor in second language learning because it can support understanding while also creating challenges in English communication.